Optimalisasi Pengendalian Persediaan Bahan Baku Dalam Peningkatan Efisiensi Operasional Pada UMKM Kebab dan Burger Foursist di Kota Tarakan - Hidayat, Nurul; Warani, Tofel; Pangestu, Muhamad Agung; Mikal, Ribkayanti (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting regional economic development. However, inefficient inventory management remains a significant challenge in operational effectiveness. This study aims to analyze raw material inventory control at Kebab & Burger Foursist MSME in Tarakan City using the Economic Order Quantity (EOQ) and Reorder Point (ROP) methods. A descriptive quantitative approach was employed, utilizing annual sales data, ordering costs, and storage costs of main raw materials. The results indicate that the implementation of EOQ and ROP effectively determines the optimal purchase quantity and reorder timing, thereby minimizing total inventory costs and reducing the risk of stockouts or overstocking. The use of POM-QM for Windows software enhances the accuracy of the analysis. The implications of this study offer practical solutions for MSME actors in managing raw material procurement more efficiently and systematically.